JEJAK PERADABAN DI BUKIT ONDONGAN: STUDI ARKEOLOGI-HISTORIS MAKAM RAJA-RAJA BANGGAE SEBAGAI SIMBOL KEJAYAAN ISLAM DI MAJENE - Yusbayani Yusbayani; Andi Abdul Hamzah; Darussalam Syamsuddin (FASTABIQ: JURNAL STUDI ISLAM, 2026)
This study examines the Banggae Royal Tomb Complex on Ondongan Hill, Pangali-ali Village, Banggae District, Majene Regency, West Sulawesi, as an archaeological artifact and a symbol of Islamic civilization in the Mandar region. Designated as a National Cultural Heritage since 1999, this site is the largest traditional burial complex in West Sulawesi, comprising 471 tombs spread across 1.6 hectares, yet it has received no comprehensive or systematic scientific study to date. This research employs a qualitative approach combining field archaeology with symbolic hermeneutics. Data were collected through structured field observation of all 471 tombs, photographic and technical documentation, and an extensive literature review of archaeological, historiographical, and ethnographic sources. Quantitative analysis was applied to tombstone dimensions, spatial distribution of graves, and frequency of decorative motifs. Findings reveal that the complex contains tombs spanning the 16th to 20th centuries, organized into five dynastic zones. Typological analysis identified four tombstone categories — flat-upright, crown, cylindrical, and composite — with coral stone as the dominant material. The most significant finding is the presence of swastika symbols on 30.4% of tombstones alongside Arabic calligraphy and Islamic geometric motifs, constituting compelling evidence that Islamization in Mandar was acculturative and dialogic rather than substitutive. Through symbolic hermeneutic interpretation, the tombstones can be read as texts encoding theological, political, and cultural meanings simultaneously. The selection of Ondongan Hill reflects the vertical cosmology of Mandar society, which regards elevated terrain as sacred space — a concept that was not eliminated but harmonized with Islamic values, making this site a living monument to centuries of synthesis among Austronesian, Hindu-Buddhist, and Islamic traditions. On a broader scale, the complex stands as a strategic node in the maritime Islamic burial site network across the Indonesian archipelago, reaffirming that Islamization in Indonesia was an adaptive, contextual, and culturally negotiated process.